Struttura e narratore ne I Promessi Sposi di Alessandro Manzoni - Samir, Aseel; Salama, Rabie (Romanica Silesiana, 2020)
In the early 19th century, the Italian literature did not have a mature novel, as is known today. The Italian novelist, Manzoni, and his masterpiece The Betrothed, set a solid basis for the contemporary Italian novel; thanks to its’ narrative characteristics that helped the novelist in achieving different reformative goals, woven stupendously with fictional, historical and realistic threads. The main purpose of this study is to apply an analytical and thematic approach on the structure and narrator of the novel. Furthermore, the research aims to distinguish the main artistic characteristics adopted from the European historical novel. The study then focuses on analyzing the function of the anonymous author’s fictional frame and how it created a diversity in the narrative levels. The research also highlights the importance of the omniscient narrator, the strong relations between the narrator and the narratee, the different narrative perspectives, and finally the polyphony: techniques that enhanced the realistic dimension of the novel.